Evidence-based quality standards improve prognosis in colon cancer care - Trautmann, Freya; Weitz, Jürgen; Schmitt, Jochen Maximilian (European journal of surgical oncology, 2018)
Background - Colon cancer requires interdisciplinary care with quality of initial surgical treatment being a major prognostic factor. Implementation of quality standards based on structural and procedural indicators in routine care via certification (Germany) or accreditation (USA) is an established quality assurance method. However, evidence on effects is scarce. We undertook a population-based cohort study to investigate the effectiveness of colon cancer care in certified vs non-certified hospitals. - Materials and methods - We utilized data of a large statutory health insurance including in- and outpatient data from 2005 to 2015 of >2 million individuals from Saxony, Germany. Case definitions were based on diagnosis, medical procedures and prescriptions. Patients treated in certified hospitals (CH) were compared to patients treated in non-certified hospitals (NCH) using logistic and Cox regression models adjusting for relevant confounders concerning overall survival (OS), disease-specific survival (DSS), 30-day mortality, recurrence, complications and second resections within 6 months after first resection (SR). - Results - Overall, 6186 patients with incident colon cancer undergoing surgery were identified (mean age 74.1 ± 11.0 years, 51.1% male) with 2120 (34.3%) patients treated in a CH. Confounder-adjusted regression models indicated positive effects in CH on OS (HR = 0.90, 95%CI: 0.83-0.97), DSS (HR = 0.71, 95%CI: 0.57-0.88), 30-day mortality (OR = 0.69, 95%CI: 0.55-0.87) and SR (OR = 0.51, 95%CI: 0.30-0.87). These results remained stable after adjustment for hospital volume. 30-day mortality in 2014 was 41% lower in CH (7.4%) compared to NCH (12.6%). - Conclusions - This study indicates that the implementation and assurance of evidence-based quality standards has substantial positive effects on various patient-relevant outcomes in colon cancer care.
Gesehen am 16.05.2019